Bibliometric analysis of COVID-19 editorial materials in the beginning stage of the pandemic - Ho, Yuh Shan; López-López, Wilson; Vega-Arce, Maribel; Salas, Gonzalo; Urzúa, Alfonso; Torres-Fernández, Ivelisse (Malaysian Journal of Library and Information Science, 2021)
Editorial materials express the opinions of the scientific community and guides the publication foci; thus, providing insight into the dynamics of the knowledge ecosystem in a scenario that impacts innovation and public policies. The purpose of this bibliometric analysis was to identify the main characteristics of the editorial materials published at the beginning stage of the COVID-19 pandemic, published between 2019 and April 30, 2020 and indexed in the Web of Science Core Collection. A total of 537 editorial materials were written by 1,455 authors, primarily in English, and in the general and internal medicine category. The majority of these editorial materials were published in the British Medical Journal and Lancet. The United States, China, and United Kingdom had the most editorial materials, with Harvard Medical School, Imperial College, and Oxford University were the leading universities. Richard Horton was the most prolific author and the editorial material by Hui et al. (2020) was the most cited. In the initial stage of COVID-19, editorial materials reflected contingent aspects of the course of the infection at the global, regional, and national levels. In the emerging and rapidly developing crisis of COVID-19, editorial materials allow the scientific community to engage in the ongoing discussions. Analysis of editorial materials fosters the understanding of the dynamics of the knowledge ecosystem.